Murder of a chocolate-covered cherry [large type] - Swanson, Denise (Swanson, Denise. Scumble River mysteries., 2008)
Grandma Sal's Soup-To-Nuts Cooking Challenge is coming to town, and Skye Denison is entering. And though she can't solve the mystery of the perfect mousse, murder is another story. Because a cocky contestant has been found delectably drowned in a chocolate fountain...